EFFECT OF SOCIOECONOMIC FACTORS ON CERTIFYING CEREAL SEED CLASSES FARMS (EVIDENCE FROM IRAN) - mohammad mazhari; mohammad tabeei (علوم و فناوری بذر ایران)
The production of cereal seeds including wheat and barley as one of the most important strategic products is the largest seed production cycle in the country. One of the most important goals in the agricultural sector is the production and distribution of standardized and certified grain crops in a wide range. In this regard, the Agricultural Jihad organization and the private sector in Khorasan Razavi province have signed contract with the contractors who have the necessary conditions for the production of cereal seeds. During the growth period, the relevant technical experts conducted alternate visits to the farms to confirm seed propagation farms. The important problem with this is that around 30% of these farms do not endorse for many reasons, despite the high cost. Therefore, the purpose of this research is to investigate the economic and management factors affecting the confirmation of wheat and barley seed producers' farms. In the present study, by using cross-sectional data of 1391-92 and using Logit model, the factors affecting the confirmation of wheat and barley fields were investigated. The results showed that the variables of education level, total cropping area, use of technical experts, satisfaction of seed price and satisfaction of payment method by seed purchase companies had a positive and significant relationship, and the number of cultivars had a negative and significant relationship With dependent variable, confirmation of seed farms.